1992
DOI: 10.1177/036354659202000218
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in adolescent and preadolescent boys at two large wrestling tournaments

Abstract: We evaluated injury patterns at two wrestling tournaments involving 1742 participants, aged 6 to 16 years. The overall injury rate was 12.7%. Injuries requiring withdrawal from the tournament occurred in 4.6% of the participants. Of all participants, 3% sustained an injury in their first match, and 1.1% sustained an injury during their first match that required withdrawal from the tournament. Primary areas of injury were the upper extremity (33%) and the neck and back (24%). Wilcoxon rank-sum tests revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…Most studies have found no statistically significant relationship between injury and weight class. 8, 13-15, 29, 31 Lorish et al 18 found a trend toward increased injury with increasing weight, but this proved to be not statistically significant with multiple regression analysis. The present study showed a trend toward more injuries in the middle weights (54%), but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most studies have found no statistically significant relationship between injury and weight class. 8, 13-15, 29, 31 Lorish et al 18 found a trend toward increased injury with increasing weight, but this proved to be not statistically significant with multiple regression analysis. The present study showed a trend toward more injuries in the middle weights (54%), but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…28, No. 4, 2000 High School Wrestling Injuries 513 significant relationship to injury include period of the match, 31 score of the match, 15 successive tournament matches, 8,18,29 and years of experience. 31 We did find an increased risk of injury in wrestlers with 3 or more years of experience, but we did not study match scores or tournament-related variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary published data on middle school-aged boy wrestlers are limited to tournament competition data, 46 with no practice injury data available. To our knowledge, injury data for female wrestlers at any level have not been reported.…”
Section: Individual Sport: Wrestlingmentioning
confidence: 99%
“…In the only study with the percentage of knee injuries below 10%, Lorish et al described injuries in tournaments to wrestlers aged 6 - 16 years (12). The knee injuries, in our study also were quite high comprising 37.7% of all of all injuries reported.…”
Section: Discussionmentioning
confidence: 99%